Tadalafil-Loaded Self-Nanoemulsifying Chewable Tablets for Improved Bioavailability: Design, In Vitro, and In Vivo Testing - Hany S. M. Ali; Sameh A. Ahmed; Abdulmalik A. Alqurshi; Ali M. Alalawi; Ahmed M. Shehata; Yaser M. Alahmadi (MDPI AG, 2022)
This research aimed to develop innovative self-nanoemulsifying chewable tablets (SNECT) to increase oral bioavailability of tadalafil (TDL), a nearly insoluble phosphodiesterase-5 inhibitor. Cinnamon essential oil, PEG 40 hydrogenated castor oil (Cremophor® RH 40), and polyethylene glycol 400 served as the oil, surfactant, and cosurfactant in the nanoemulsifying system, respectively. Primary liquid self-nanoemulsifying delivery systems (L-SNEDDS) were designed using phase diagrams and tested for dispersibility, droplet size, self-emulsifying capability, and thermodynamic stability. Adsorption on a carrier mix of silicon dioxide and microcrystalline cellulose was exploited to solidify the optimum L-SNEDDS formulation as self-nanoemulsifying granules (SNEG). Lack of crystalline TDL within the granules was verified by DSC and XRPD. SNEG were able to create a nanoemulsion instantaneously (165 nm), a little larger than the original nanoemulsion (159 nm). SNECT were fabricated by compressing SNEG with appropriate excipients. The obtained SNECT retained their quick dispersibility dissolving 84% of TDL within 30 min compared to only 18% dissolution from tablets of unprocessed TDL. A pharmacokinetic study in Sprague-Dawley rats showed a significant increase in Cmax (2.3-fold) and AUC0-24 h (5.33-fold) of SNECT relative to the unprocessed TDL-tablet (p < 0.05). The stability of TDL-SNECT was checked against dilutions with simulated GI fluids. In addition, accelerated stability tests were performed for three months at 40 ± 2 °C and 75% relative humidity. Results revealed the absence of obvious changes in size, PDI, or other tablet parameters before and after testing. In conclusion, current findings illustrated effectiveness of SNECT to enhance TDL dissolution and bioavailability in addition to facilitating dose administration.